Literasi Memulai Usaha Baru Dan Pengelolaan Keuangan Sederhana Bagi Usaha Kecil Di Kelurahan Jakasampurna Bekasi - Dade Nurdiniah; Kristiana Widiawati; Nurul Kamila (LPMP Imperium, 2024)
Small businesses play an important role in driving the local economy, creating jobs and supporting inclusive economic growth. Many small businesses are run by the community, but most business actors are still confused about starting a new business and do not have adequate knowledge and skills in managing their business finances. This service activity was carried out with the aim of providing literacy in starting a new business and simple financial management for small businesses in Jakasampurna Bekasi Village. This activity was carried out on 11 and 21 August 2023 at Jakasampurna Bekasi Village and was carried out in two stages, namely delivery of material and evaluation. Participants in this activity were 20 mothers who were members of the Family Welfare Empowerment (PKK). The final result of this activity was an increase in participants' understanding of the material presented, this was proven through the results of the pre-test and post-test which before taking part in the literacy activity the level of participants' understanding was 50-80% and after taking part in literacy the level of understanding of the participants increased to 80-100 %, and there was a participant satisfaction level of 91% who said they were very satisfied. The very high level of participant satisfaction, namely 91%, shows that this activity has fulfilled the participants' expectations in starting a new business and simple financial management.